2014
DOI: 10.1021/sc5003787
|View full text |Cite
|
Sign up to set email alerts
|

Green Method for Production of Cellulose Multifilament from Cellulose Carbamate on a Pilot Scale

Abstract: In the cellulose industry, the viscose process is still occupying the leading position, although this process generates several environmentally hazardous byproducts. Here we report a novel method for the production of cellulose multifilament from cellulose carbamate (CC) on a pilot scale. In this method, CC was first prepared efficiently by microwave heating; it was then dissolved in NaOH/ZnO aqueous solutions through a freezing–thawing process. Wet spinning of the CC solution was performed on a pilot-scale ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…As illustrated in Figure 10, the chemical shifts of C1 (105.2 ppm), C4 (87.8) ppm, C5 (75.0 ppm) and C6 (62.8 ppm) for the both parts are almost the same as those for regenerated cellulose fibers from CC-NaOH/ ZnO solution. 33,34 In a comparison of the dissolved part, the C4 peak of the insoluble was relatively weak. The previous studies revealed thermal treatment of cellulose would lead to decrease of bands associated with hydroxyl and glycosidic groups, especially in the C4 signal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As illustrated in Figure 10, the chemical shifts of C1 (105.2 ppm), C4 (87.8) ppm, C5 (75.0 ppm) and C6 (62.8 ppm) for the both parts are almost the same as those for regenerated cellulose fibers from CC-NaOH/ ZnO solution. 33,34 In a comparison of the dissolved part, the C4 peak of the insoluble was relatively weak. The previous studies revealed thermal treatment of cellulose would lead to decrease of bands associated with hydroxyl and glycosidic groups, especially in the C4 signal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, there were neither organic transfer mediums (xylene) nor catalytic agents (sodium carbonate) used, and the energy savings was over 50% when compared to the conventional synthesis of CC. 31 Furthermore, the ZnO could be well recovered from the coagulation bath and washing water by adding CaO through the two-step precipitation method. 46 Therefore, the novel carbamate process demonstrated great potential for the production of high-quality cellulose multifilament in a much more environmentally friendly and economic way, in addition to potential for applications in the development of viscose-like products.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Most recently, it was determined that the solubility of CC could be significantly improved with the addition of a small amount of ZnO to the NaOH solution. 31 Moreover, green methods for the production of cellulose multifilament and membranes from CC have been reported. 31,32 The lower cost and lower toxicity of our novel carbamate method, and its relative ease for wet spinning, exhibited some good promises for the development of a more economic and environmently friendly process for regeneration of RC fibers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A process, which is analogous to the viscose process, is the carbamate process, where cellulose is reacted with urea to form cellulose carbamate [70]. Cellulose carbamate can then be processed in a similar manner as cellulose xanthate, but without the release of harmful compounds [71]. However, the process has not yet reached commercialization, most likely due to insufficient fiber properties.…”
Section: Aqueous Alkalimentioning
confidence: 99%